MY SAY: What waste in a hungry world - Abd Razak, Dzulkifli (2009)
One of the characteristics of a highincome economy appears to be the correspondingly high amount of waste that it generates compared with a lowincome economy. In fact, as countries graduate from a lower to a higher level economy, the amount of waste they generate goes up accordingly. Reports show that many Asian economies are facing a similar predicament as they benchmark themselves against existing highincome countries. More recently, China has been singled out for the amount of waste it produces as its economy chalks up an unprecedented performance, even as the world is going through a difficult time. China, according to an International Herald Tribune report on Aug 13, has surpassed the US as "the world's largest producer of household garbage".